Microbial Communities in a Serpentinizing Aquifer Are Assembled through Strong Concurrent Dispersal Limitation and Selection - Lindsay I. Putman (American Society for Microbiology, 2021)
Microbial communities existing under extreme or stressful conditions have long been thought to be structured primarily by deterministic processes. The application of macroecology theory and modeling to microbial communities in recent years has spurred assessment of assembly processes in microbial communities, revealing that both stochastic and deterministic processes are at play to different extents within natural environments.